SELF DISCLOSURE PADA ANAK KORBAN PERCERAIAN MELALUI TIK TOK - Saputri, Safira Marsha; Pratiwi, Aprilyanti (Jurnal Insani, 2022)
Divorce is the end of the relationship between husband and wife in one family. In this case the divorce victim's child sees his parents directly quarrel or commit physical crimes against each other in a fight that ends in divorce. Freeing a child divorce victim specifically in middle-drunk adolescents is difficult to disclose themselves to others. Self-disclosure in divorced children through Tik Tok. The concepts used in this study are self-disclosure, child victims of divorce, social media, and adolescents. The paradigm used is post positivism by using qualitative descriptive. The unit of analysis is the individual, the child of the divorce victim. Data collection techniques used are through interviews and documentation. The research instrument is the research itself using Miles and Huberman's data analysis techniques. In this study, researchers used triangulation to test the validity of research data. The results of this study were found about divorced child victims doing self-disclosure through Tik Tok by uploading videos with music as a background instrument that discusses the family they are dealing with. One factor that encourages child victims to self-disclose through Tik Tok is because Tik Tok considers the most appropriate media and the response obtained is positive, so this can provide good feedback and self-disclosure can be done clearly.